2005
DOI: 10.1007/s10551-005-3439-3
|View full text |Cite
|
Sign up to set email alerts
|

Similarities in Business and IT Professional Ethics: The Need for and Development of A Comprehensive Code of Ethics

Abstract: The study of business ethics has led to the development of various principles that are the foundation of good and ethical business practices. A corresponding study of Information Technology (IT) professionals' ethics has led to the conclusion that good ethics in the development and uses of information technology correspond to the basic business principle that good ethics is good business. Ergo, good business ethics practiced by IT professionals is good IT ethics and vice versa. IT professionals are professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 18 publications
(32 reference statements)
0
17
0
Order By: Relevance
“…In the context of organizations, intervention with respect to UITU often takes the form of business codes. 2 In the case of IT use, business codes are seen as a necessary intervention to promote good business practices (Payne and Landry, 2005). Issued by IT managers or senior managers, they aim to clarify responsibilities (Johnson and Mulvey, 1995;Oz, 1992) and influence behavior (Leonard and Cronan, 2001).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In the context of organizations, intervention with respect to UITU often takes the form of business codes. 2 In the case of IT use, business codes are seen as a necessary intervention to promote good business practices (Payne and Landry, 2005). Issued by IT managers or senior managers, they aim to clarify responsibilities (Johnson and Mulvey, 1995;Oz, 1992) and influence behavior (Leonard and Cronan, 2001).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Congruent with the literature, a code of ethics is empirically proven to influence good governance. For example, Payne and Landry (2005) found that a code of ethics influences good governance practices. Payne and Landry's (2005) study revealed seven core values (consistency, respect individual, autonomy, integrity, justice, utility, and competence) as concepts that serve as professional attributes towards good business practices.…”
Section: Codes Of Ethical Conductmentioning
confidence: 99%
“…For example, Payne and Landry (2005) found that a code of ethics influences good governance practices. Payne and Landry's (2005) study revealed seven core values (consistency, respect individual, autonomy, integrity, justice, utility, and competence) as concepts that serve as professional attributes towards good business practices. Code of ethics, as perceived by Schwartz, Dunfee, and Kline (2005), includes values such as honesty, loyalty, integrity, responsibility, citizenship and fairness.…”
Section: Codes Of Ethical Conductmentioning
confidence: 99%
“…In the consideration of data mining, several constituents are more important than others (Payne & Landry 2005) because the positive or the negative effects of actions exerted on various stakeholders can differ considerably. The main criterion, then, for the authors' selection of stakeholders to review was the magnitude of harm that might be felt by the stakeholder if the data mining process were not executed in an ethical fashion.…”
Section: The Practical and Ethical Stakes For Stakeholdersmentioning
confidence: 99%